The Role Of Organizational Citizenship Behavior As Mediator To The Relationship Between Leadership Styles And Organizational Commitment - Maki, Mohamed Abdulaziz Mohsen (2020)
The purpose of this study is to explore the relationship between leadership styles, organizational commitment, and organizational citizenship behavior as a mediating variable in both public and private sector leaders in the Kingdom of Bahrain. Organizational citizenship behavior as an essential area of study were in debate about the positive and negative consequences through the literatures, while most of the studies were support the relationship of organizational commitment that leads to organizational citizenship behavior, there are other studies that support the opposite of organizational citizenship behavior which leads to organizational commitment. Therefore, the use of mediating variable gives more insight into the relationship between the dependent and independent variables and contributes to the clarity of conclusions. Besides, it focuses on the process by which one variable affects another. In this study, exploration of these variables and their impacts has had been presented. Previous studies were in a debate; some researchers confirm a positive significant relationship between both leadership styles and organizational commitment, while others concluded that transformational leadership is associated with organizational commitment.